Officer Compliance Regarding Implementation of The Surgical Safety Checklist Based on Theory of Planned Behavior in Patients at The Central Surgical Installation of Regional Public Service Agency Benyamin Guluh Hospital, Kolaka District - Usman, Usman; Saafi, La Ode; Munir, Sanihu; Hariadhin Depu, Anry (Waluya The International Science of Health Journal, 2025)
Introduction: The importance of compliance behavior of the application of the surgical safety checklist to the treatment process by ensuring that specific tasks are completed and indirectly by improving communication among the surgical team in each surgical procedure to minimize surgical errors. Based on medical record data at Regional Public Service Agency Benyamin Guluh Hospital, Kolaka Regency, it was found that the number of patients undergoing operative procedures in 2021 was 1,456 patients, in 2022 there were 2,195 patients, in 2023 there were 2,839 patients. Method: This type of research is quantitative research with a cross sectional study approach The population is all health workers (surgical team) in charge of the Central Surgical Installation of Benyamin Guluh Hospital, Kolaka Regency in 2023, totaling 35 people. Sample withdrawal using Purposive Sampling with a sample size of 26 respondents. Statistical tests used are Structural Equation Modeling and Partial Least Square (SEM PLS) models. Result: This study shows that behavior beliefs affect officer compliance regarding the implementation of the surgical safety checklist. Behavioral beliefs have no effect on control beliefs. Normative control (normative beliefs) affects control beliefs. Normative control (normative beliefs) affects officer compliance regarding the implementation of the surgical safety checklist. Control beliefs affect officer compliance regarding the implementation of the surgical safety checklist. Conclusion: The conclusion of this study is behavioral beliefs, normative control, confidence control have a significant effect on officer compliance regarding the implementation of the surgical safety checklist.